Fluid dynamics of controllable synthesis of micro-fine powder particles using Taylor-Couette flow reactors - Xue, Chenyang (2021)
Synthesis of fine particles is widely encountered in many applications. Typical examples can be found in fabrication of pigments, ceramics, pharmaceuticals and bio-chemicals among others. During the whole process of particle synthesis, one particle will engage several periods such as nucleation, particle growth, aggregation and breakage. The reaction environment provided by chemical reactors plays a crucial role in particle synthesis. The control of particle properties such as size and morphology are mostly determined by the control of fluid dynamics in the reactors. Therefore, the purpose of this PhD research is to investigate the fluid dynamics in Taylor-Couette (TC) flow reactors for the application of controllable synthesis of micro-fine powder particles. The main work and outcomes can be summarised as: